Pengaruh orientasi kewirausahaan dan Orientasi Pasar Terhadap Kinera Pemasaran Melalui Keunggulan Bersaing sebagai Variabel Intervening - Mitha Fajri Fillanov; Lili Karmela Fitriani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The problem in this study is the large number of MSMEs today which causes businesscontinuity to experience a high level of competition, especially MSMEs that produce similarproducts. Like other MSMEs, almost all MSMEs in Kuningan Regency have also experiencedups and downs, this shows that the marketing performance of these business actors has notbeen optimal. This study aims to examine and analyze the influence of entrepreneurialorientation and market orientation on marketing performance. To examine and analyze theinfluence of entrepreneurial orientation and market orientation on competitive advantage. Toreview and analyze competitive advantages affecting marketing performance. To examine andanalyze whether competitive advantage can mediate the influence of entrepreneurialorientation on marketing performance. To examine and analyze whether competitiveadvantage can mediate the influence of market orientation on marketing performance. Thisresearch was carried out on MSMEs in Kuningan Regency which were fostered by the Tradeand Industry SME Cooperative Office of Kuningan Regency as many as 53,771 MSMEs, asample of 140 MSMEs. The results of the data analysis resulted in conclusions: 1)entrepreneurial orientation has a positive and significant effect on marketing performance. 2)Market orientation has a positive and significant effect on marketing performance. 3)Entrepreneurial orientation has a positive and significant effect on competitive advantage. 4)Market orientation has a positive but not significant effect on competitive advantage. 5)Competitive advantage has a positive but not significant effect on marketing performance. 6)the absence of the influence of entrepreneurial orientation on marketing performance throughcompetitive advantage. 7) the absence of market orientation influence on marketingperformance through competitive advantage